Encyclopedia of Chinese Language and Linguistics Online - Sybesma, Rint, 1960-; Behr, Wolfgang, 1965-; Myers, James; Gu, Yueguo; Handel, Zev J.; Huang, Cheng-Teh James, 1948- (Brill, 2017)
The Encyclopedia of Chinese Language and Linguistics offers a systematic and comprehensive overview of the languages of China and the different ways in which they are and have been studied. It provides authoritative treatment of all important aspects of the languages spoken in China, today and in the past, from many different angles, as well as the different linguistic traditions they have been investigated in.